SERBIA’S DIPLOMACY IN DETERRENCE - Blagojevic, Veljko (Serbian political thought, 2023)
Diplomacy represents the first line of promotion and defense of national interests and one of the sources of power, together with military, economic, information and others. The importance and complexity of diplomacy for Serbia in the conditions of modern international relations can perhaps best be seen in terms of deterrence in conditions when a major war is being waged on European soil, which will certainly have long-term consequences for the international system. When one adds to this the unresolved problems from the period of the wars for the Yugoslav heritage, especially the problem of the status of Kosovo and Metohija, it is certain that Serbia must constantly strive to use all national potentials in the best possible way for a comprehensive and credible deterrence under the conditions of the application of the policy of military neutrality, which only further complicates the challenges. The effectiveness of diplomacy is one of the key prerequisites for successful deterrence, but its synergy with other instruments of foreign policy cannot be reliably realized without the concept of strategic communication. The goal of the work is to rely on a realistic theoretical basis, by analyzing the functions of diplomacy, to see its importance for successful deterrence and the necessity of synchronized action with other foreign policy tools, which are developed primarily for the purpose of deterrence, but can also be interpreted differently if diplomacy fails to avoid pitfalls. security dilemmas.